2022
DOI: 10.3389/fmed.2022.877764
|View full text |Cite
|
Sign up to set email alerts
|

Mass Media Use to Learn About COVID-19 and the Non-intention to Be Vaccinated Against COVID-19 in Latin America and Caribbean Countries

Abstract: BackgroundThe Latin American and Caribbean (LAC) region has been one of the regions most affected by the COVID-19 pandemic, with countries presenting some of the highest numbers of cases and deaths from this disease in the world. Despite this, vaccination intention is not homogeneous in the region, and no study has evaluated the influence of the mass media on vaccination intention. The objective of this study was to evaluate the association between the use of mass media to learn about COVID-19 and the non-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Even though vaccines are essential for controlling communicable diseases such as monkeypox [16,17], there are multiple motivations for reluctance to vaccines, including fear to their negative adverse effects, misinformation and its impact, or distrust of medical personnel or the health system, among others [18,19]. Likewise, sociodemographic factors such as age, sex, and geographical residence zone would be connected differently with vaccine disposition subject on the context where them are investigated [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Even though vaccines are essential for controlling communicable diseases such as monkeypox [16,17], there are multiple motivations for reluctance to vaccines, including fear to their negative adverse effects, misinformation and its impact, or distrust of medical personnel or the health system, among others [18,19]. Likewise, sociodemographic factors such as age, sex, and geographical residence zone would be connected differently with vaccine disposition subject on the context where them are investigated [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have indicated that in general, people are hesitant to be vaccinated in response to the current monkeypox outbreak [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. There were numerous reasons cited for vaccine hesitancy, including the fear for negative side effects, misinformation, and mistrust of medical staff or the healthcare system [ 73 , 74 ]. Lack of knowledge and inappropriate attitudes of healthcare workers (HCWs) themselves might have a negative impact on their selection of treatment for themselves, and this might also affect the steps taken for primary prevention, early identification, and prompt intervention involving patients [ 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%